A Case of Clear Cell Meningioma With Tyrosine-Rich Crystals. (August 2013) - Schollenberg, Erica; Easton, Alexander S.
We present a case of clear cell meningioma with unusual clinical and pathologic features. The patient was a 54-year-old man who underwent laminectomy and durotomy for an intradural tumor in the lumbar spinal canal. Sections showed a predominance of dense collagenous tissue with irregularly shaped and irregularly sized magenta-colored extracellular deposits. On electron microscopy, these deposits were osmiophilic and "petaloid." The final diagnosis of clear cell meningioma rested on relatively inconspicuous intervening nests of glycogen-containing clear cells that were positive for epithelial membrane antigen. The unusual extracellular deposits seen in this case have previously been characterized as tyrosine-rich crystals of the type most commonly seen in salivary gland tumors. Recognition of this tumor as a clear cell meningioma, despite misleading clinical features and initially challenging histologic findings, is not only a matter of diagnostic accuracy but also imparts important prognostic information.